Development strategy of candlenut oil business toward a new paradigm for the utilization of non-timber forest products - Jumiyati, Sri; Haeruddin; Bachri, Syaiful; Nawir, Burhanuddin (Holistic: Journal of Tropical Agriculture Sciences, 2024)
In an effort to realize productive and sustainable forest management in a unified and comprehensive forestry development unit so that the economic (Sustainable Production), social (Sustainable Social and economic) and environmental (Ecological Sustainable) benefits for all parties based on the identification of the potential superiority of regional commodities, Forest Management Unit (KPH) has compiled a business development plan to improve the economic community in and around the forest, through the development of various productive businesses utilizing timber and non-timber forest products (NTFPs). Therefore, it is necessary to develop a business strategy to overcome the weaknesses and threats by utilizing internal and external strengths and opportunities in efforts to develop sustainable rural agro-industry. The study was conducted at a pilot location of the KPH Kulawi candlenut oil processing business, Central Sulawesi Province. Communication and observation techniques were carried out using a questionnaire through individual interviews and group interviews. While the business development strategy is carried out through focus group discussions (FGDs) involving stakeholders, namely the KPH, raw material producing farmers, processing farmers, target village governments, local governments, the business world and academics with a total of 15 respondents. Based on the SWOT Matrix, The choice of strategies that can be applied are resource optimization, increasing product quality at competitive prices, increasing managerial skills and HR skills and efficiency in production costs. While policies that can support business development include easy access to capital, facilitating export bureaucracy mechanisms and the existence of business associations as a source of market and price information.